2014
DOI: 10.1021/cg4009637
|View full text |Cite
|
Sign up to set email alerts
|

Hydroxypropyl Methylcellulose as a Novel Tool for Isothermal Solution Crystallization of Micronized Paracetamol

Abstract: Pulmonary inhalation is increasingly being selected as a preferred route for the delivery of both small and large drug macromolecules for the treatment of a range of pathologies. The direct crystallization of micronized powders, in particular, paracetamol, remains difficult, as it requires the ability to work in high solution supersaturations where agglomeration, wall crusting, and heterogeneous nucleation hinder the control of crystal size and crystal size distribution. Polymer additives are recognized to hel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 23 publications
1
18
0
Order By: Relevance
“…It can be explained by HPMC molecules forming hydrogen bonds with water, which can immobilize water molecules and hinder their incorporation into the crystal lattice. 26 , 56 , 57 Similar behavior was observed by Tian et al, 58 who found that the phase transformation of anhydrous carbamazepine polymorphic forms I and III to the dihydrate was inhibited in aqueous HPMC solutions. In addition, HPMC can form hydrogen bonds with PRX via OH groups in HPMC and PRX molecules.…”
Section: Resultssupporting
confidence: 71%
See 1 more Smart Citation
“…It can be explained by HPMC molecules forming hydrogen bonds with water, which can immobilize water molecules and hinder their incorporation into the crystal lattice. 26 , 56 , 57 Similar behavior was observed by Tian et al, 58 who found that the phase transformation of anhydrous carbamazepine polymorphic forms I and III to the dihydrate was inhibited in aqueous HPMC solutions. In addition, HPMC can form hydrogen bonds with PRX via OH groups in HPMC and PRX molecules.…”
Section: Resultssupporting
confidence: 71%
“… 13 17 It has been used to prepare ultrafine powders and micro-/nanodispersions of many APIs, including budesonide, 18 danazol, 19 beclomethasone dipropionate, 20 griseofulvin and fenofibrate, 21 salbutamol sulfate, 22 prednisolone, 23 atorvastatin, 24 l -glutamic acid, 25 and paracetamol. 26 …”
Section: Introductionmentioning
confidence: 99%
“…[7][8][9] Borsos et al have recently developed a control strategy to tailor the shape of crystals of potassium dihydrogen phosphate using two different growth modifiers, aluminum sulphate and sodium hexametaphosphate. 10,11 In some cases impurities are deliberately added to a crystallization to engineer the growth of crystals with a desired morphology (by inhibiting growth of selected faces); these are known as additives and they can be used to control the shape of the final crystals, [12][13][14][15][16] their size [17][18][19][20] and polymorphic form. 21,22 There is a broad array of examples of the effect of structurally similar additives on crystal morphology, [23][24][25][26][27][28][29][30][31][32] including the well-known examples of urea crystallized in the presence of biuret 33 and benzamide with benzoic acid.…”
Section: Introductionmentioning
confidence: 99%
“…In solution crystallization, many studies have shown that the presence of impurities often has a great influence on the nucleation and growth of crystals, leading to changes in the polymorphic form or shape (Majumder & Nagy, ; Poornachary, Chow, & Tan, , ; Reis, Liu, Reis, & Mackley, ; Şahin, Özdemir, & Genli, ; Saleemi, Onyemelukwe, & Nagy, ; Yang, Song, Ying, Chen, & Heng, ). In fact, impurities such as dust are inevitable in an actual crystallization system.…”
Section: Introductionmentioning
confidence: 99%